Description of the immature stages and redescription of the adults of Culex (Culex) lahillei Bachmann & Casal (Diptera: Culicidae) - Laurito, Magdalena; Almirón, Walter Ricardo; Rossi, Gustavo Carlos (Zootaxa, 2011)
The pupa and fourth-instar larva of Culex (Culex) lahillei Bachmann & Casal are described and illustrated for the first time and the adults redescribed. Information is provided on the distribution, bionomics and taxonomy of the species.